1996
DOI: 10.1128/aem.62.12.4587-4593.1996
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects on bacterial metabolism of the redox dye 5-cyano-2,3-ditolyl tetrazolium chloride

Abstract: The monotetrazolium redox dye 5-cyano-2,3-ditolyl tetrazolium chloride (CTC) has been used as a vital stain of actively respiring bacteria for several years. In this study, inhibitory effects on bacterial metabolism of this redox dye have been examined in a brackish water environment (Kiel Fjord, Germany) and a freshwater environment (Elbe River, Germany). As the results from time series experiments (1 to 10 h) show, bacterial growth and respiration of the investigated natural communities were clearly reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(59 citation statements)
references
References 44 publications
4
53
0
2
Order By: Relevance
“…Further support for this conclusion comes from the low fraction of CTC-reducing cells that has also been reported for bacteria from drinking water samples or from soil [34,37]. One major reason for these low counts of CTC-reduc-ing bacteria may be the toxicity of CTC which inhibits glucose uptake and respiration, thymidine incorporation, and growth on agar plates [3].…”
Section: Ctc Reduction As a Measure Of Viabilitymentioning
confidence: 76%
See 1 more Smart Citation
“…Further support for this conclusion comes from the low fraction of CTC-reducing cells that has also been reported for bacteria from drinking water samples or from soil [34,37]. One major reason for these low counts of CTC-reduc-ing bacteria may be the toxicity of CTC which inhibits glucose uptake and respiration, thymidine incorporation, and growth on agar plates [3].…”
Section: Ctc Reduction As a Measure Of Viabilitymentioning
confidence: 76%
“…Generally less than 1% of the total number of bacterial cells which are present in natural seawater, soil, or freshwater samples can be cultured by standard laboratory methods [1^3]. However, up to 50% [4] and in some instances even 90% [5] of the bacterial cells appear to be metabolically active when assessed by the direct viable count technique [6], by microautoradiography with radiolabelled substrates [3,4,7], or by monitoring the presence of active electron transport systems in the cells with tetrazolium 0168-6496 / 99 / $20.00 ß 1999 Federation of European Microbiological Societies. Published by Elsevier Science B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Such problems have not been seen with Gram-negative organisms such as Escherichia coli where no significant difference has been observed between the CB assay, CTC assay and plate counts. In a recent review, Ullrich et al (1996) describe a growing body of evidence which suggests that CTC is unsuitable for the enumeration of bacteria in environmental samples. The possible expla-nations for obtaining lower counts by CTC than by other direct methods of enumeration were (i) not all bacteria are capable of reducing tetrazolium salts (Thom et al 1993), (ii) the assay is not sensitive enough to detect bacteria with low rates of metabolic activity (Gasol et al 1995) and (iii) although CTC has been assumed to be non-toxic to bacteria (Rodriguez et al 1992), it has been reported that bacterial metabolic activity can be directly suppressed/inhibited by CTC, causing an under-estimation of the total number of bacteria within a sample (Ullrich et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Another widely applied technique for the direct detection of viable bacteria uses the redox dye 5-cyano-2,3,4-ditolyl tetrazolium chloride (CTC) (Winding et al 1994;Oliver et al 1995;Ullrich et al 1996). This is a tetrazolium salt which is reduced by the respiratory electron transport chain to insoluble, fluorescent, formazan crystals which accumulate within individual cells.…”
Section: Introductionmentioning
confidence: 99%
“…All these method present drawbacks; DAPI binds to numerous macromolecules (Kepner and Pratt 1994), Gramnegative isolates are impermeable to FDA (Tsuji et al 1995) and rhodamine 123 (Kaprelyants and Kell 1992), and CTC has a toxic effect on bacterial metabolism (Ullrich et al 1996).…”
Section: Introductionmentioning
confidence: 99%